2020
DOI: 10.3389/fpls.2020.557672
|View full text |Cite
|
Sign up to set email alerts
|

Association Mapping and Development of Marker-Assisted Selection Tools for the Resistance to White Pine Blister Rust in the Alberta Limber Pine Populations

Abstract: demonstrates the successful translation and deployment of molecular genetic knowledge into specific MAS tools that can be easily applied in a selection or breeding program to efficiently screen MGR against WPBR in Alberta limber pine populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
(102 reference statements)
0
3
0
2
Order By: Relevance
“…The existence of Cr4 in wide ranging geographical regions indicates its complicated genetic background [ 16 , 17 , 30 ], which limits Cr4 -linked markers shared by different germplasms for development of molecular selection tools for wild stands. The present study detected sequence variations of Cr4 candidate alleles, useful for tracing Cr4 origin in limber pine populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of Cr4 in wide ranging geographical regions indicates its complicated genetic background [ 16 , 17 , 30 ], which limits Cr4 -linked markers shared by different germplasms for development of molecular selection tools for wild stands. The present study detected sequence variations of Cr4 candidate alleles, useful for tracing Cr4 origin in limber pine populations.…”
Section: Discussionmentioning
confidence: 99%
“…Cr1 , Cr2 , and Cr4 were localized on the Pinus consensus LG-2, LG-1, and LG-8, respectively [ 21 , 26 , 29 ]. A combination of linkage mapping and association study validated Cr4 or a locus very close to Cr4 for limber pine MGR in seed families that originated in both USA and Canada [ 30 ]. These comparative studies of syntenic genomic regions of closely related species identified NLR genes as R candidates, which serve as good starting points for the positional cloning of five-needle pine R genes against C. ribicola [ 24 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…SNP sangat efektif digunakan sebagai marka molekuler untuk studi genetik (Qi et al, 2017) dan setiap SNP berasosiasi dengan ekspresi gen (J. J. Liu et al, 2020). Penelitian sebelumnya telah mengembangkan marka SNAP (Single Nucleotide Amplified Polymorphism) berdasarkan sekuens transkriptomik pada lobak (Raphanus sativus L.) Wang et al, 2017), namun informasi SNP dari transkriptomik pada tanaman kelapa sawit untuk marka molekuler ketahanan GD belum dimanfaatkan secara optimal (Rosli et al, 2018).…”
Section: Rokhana Faizahunclassified
“…Tidak disebutkan OPGP project (Herrero et al, 2020) Rokhana Faizah biomolekuler masih diaplikasikan untuk proses seleksi karakteristik spesifik dalam pemuliaan tanaman (Bohry et al, 2021;Jang & Lee, 2021; J. J. Liu et al, 2020). Beberapa karakter penting pada kelapa sawit telah diseleksi menggunakan penanda molekuler, antara lain ketebalan cangkang, pertambahan hasil dan tinggi tanaman, konstruksi peta keterkaitan, kandungan asam lemak, morfologi dan sifat terkait hasil, perkembangan kalus, dan tanaman tahan Ganoderma (Tabel 1) .…”
Section: Opgp Projectunclassified
“…The underpinning of the constant improvement of rice cultivars is the abundant phenotypic and genetic diversity that resides within domesticated populations and wild relatives. The classical approach of intentional interbreeding of closely related individuals to create new cultivars with desirable traits require great effort and long duration to produce several generations, which serves as a barrier to meet the increasing requirements of food needs and maintaining global food security (He et al 2014;Liu et al 2020). Therefore, an application of molecular plant breeding known as marker-assisted breeding, capable of discovering phenotypic variation by deploying markers linked to QTLs responsible for desirable traits, became popular.…”
Section: Introductionmentioning
confidence: 99%